Analyzing Digital Utility App Adoption: A UTAUT Approach on PLN Mobile with Technological Literacy as a Moderator - Adi Susantyo, Ignatius; Yuldinawati, Lia; Apsari Sugiat, Maria (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
This study examines customers' determinants of behavioral intention to utilize the PLN Mobile application using the Unified Theory of Acceptance and Use of Technology (UTAUT) with technological literacy as a moderating variable. The data were collected from 399 respondents in the UP3 Western Flores Area using purposive sampling and analyzed by Partial Least Squares Structural Equation Modeling (PLS-SEM). The model demonstrated adequate reliability and validity (AVE > 0.5; composite reliability > 0.7) with R² = 0.62 for behavioral intention. Results indicate that performance expectancy, perceived usefulness, social influence, and facilitating conditions significantly influence intention to use the app, β = 0.21–0.34, p < 0.05, while trust and hedonic motivation were not significant. Technological literacy cemented the relationship between intention and real use, emphasizing digital capability as a key adoption driver. Active usage is minimal amid high download rates. The findings provide theoretical contributions to digital service adoption models and practical implications for facilitating user support, literacy programs, and mobile utility system introduction.